Camel Bite Associated with Depressed Skull Fracture with Rapidly Spreading Subgaleal Cellulitis - Shaymaa Al-Umran; Ahmad Abdulfattah; Faisal Alabbas; Hosam Al-Jehani (Case Reports in Infectious Diseases)
Camel bite represents a minimal proportion, and most of them are from the Middle East countries. Their infectious potential is poorly understood, and the guidelines for antimicrobial treatment are not well developed. We describe a 40-year-old male, who works as a camel herder and was bitten by a camel while he was tying it down which led to a unilateral depressed skull fracture and multiple bilateral teeth-puncture wounds in the scalp. He arrived to our emergency department 3 hours after injury. All the wounds were dry and the skin around them was healthy looking with no subcutaneous collections. CT scan of the head showed depressed skull fracture on the left temporal region. Within 12 hours, the patient developed spreading cellulitis in the scalp. This necessitated an urgent surgical intervention. The added challenge is the presence of a dural breach. Our patient presented a challenge at several levels. He presented early with clean puncture wounds that were treated according to the most agreed upon guidelines. But our novel finding of rapidly spreading cellulitis requires alteration of recommendation towards more aggressive therapeutic attitude including early surgical intervention, especially for those patients suspected of a dural tear with the depressed skull fracture, even if treated with appropriate antibiotics.